Reflections of employers’ gender preferences in job ads in India: An analysis of online job portal data - Chowdhury, Afra R; Areias, Ana C; Imaizumi, Saori; Nomura, Shinsaku; Yamauchi, Futoshi (World Bank, 2018)
Using online job portal data and probabilistic regression estimations, the paper investigates the explicit gender bias and salary gap in the Indian job market, reflected in more than 800,000 job recruitment advertisements. Exploring formal and informal sector occupations, the study finds high existence of employers’ gender bias in hiring. Explicit gender preferences are highly job specific, and it is common to mention the preferred gender in job ads, which, in general, favor men over women. Although ads for professional occupations exhibit less explicit gender bias, they are not gender neutral. In all types of professional jobs, irrespective of the share of ads with preference for men or women, on average, ads targeting men specify/offer much higher salary. Employers in elementary sectors as well as blue-collar jobs express more segregated gender preference. The findings support the existing research that argues women are more preferred in low-quality, low-status, typically lowpaid informal jobs. Targeting women for low-quality jobs explains half of the mean offered salary gap specified in ads; the rest is direct gender bias. The paper also suggests that, with the rise of new technology and sectors, gender bias in hiring in those new types of jobs is expected to decline.